(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2019)
Dividend is that portion of profits of a company which is distributable among its shareholders according to the decision taken and resolution passed in the meeting of Board of Directors. Dividend policy ploys an important role for maintaining good image of company in the capital market and in providing source of low cost finance for financing for the profitable future investment proposals. Objective of the study is to calculate the three measures of (dividend per share, earning per shore, earning retention ratio) dividend policy of the five selected compa nies Hero Motor Corporation Limited, Tide water oil company, orocle financial services software limited, lndiabulls housing finance limited and Vedanta limited and correlate the factors of dividend policy and return on share price for a period of five years. It was found from the study that only in case of lndiobulls housing finance limited DPS, EPS, ERR and ROS are positively related. So it can be said that only in case of lndiabulls housing finance limited company factors of dividend policy are positively related with ROS.